Dual effects of serum urate on stroke risk and prognosis: insights from Mendelian randomization - Chen, Shixuan; Chen, Zhenzhen; Xu, Qingqing; Jiang, Xia; Lin, Chuyong; Ji, Jing (Frontiers in Neurology, 2024)
Background To investigate the causal associations of serum urate (SUA) with stroke risk and prognosis using Mendelian randomization (MR) and the potential mediating role of stroke risk factors in the causal pathways. Methods We used the random-effects inverse variance weighting (IVW) as our primary method. We initially performed two-sample univariable MR (UVMR) to identify the causal associations of SUA (n = 437,354) with any stroke (AS, FinnGen: n = 311,635; MEGASTROKE: n = 446,696), ischemic stroke (IS, FinnGen: n = 212,774; MEGASTROKE: n = 440,328), intracranial hemorrhage (ICH, FinnGen: n = 343,663; ISGC: n = 3,026), functional outcome after ischemic stroke at 90d (n = 4,363), and motor recovery within 24 months after stroke (n = 488), and then multivariable MR (MVMR) to estimate the direct causal effects of SUA on these outcomes, adjusting for potential confounders. Finally, we further conducted a two-step MR to investigate the potential mediating role of body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), and estimated glomerular filtration rate (eGFR) in the identified causal pathways. Results Genetically predicted elevated SUA levels were significantly associated with increased risk of AS (meta-analysis: OR = 1.09, 95% CI [1.04–1.13], p = 3.69e-05) and IS (meta-analysis: OR = 1.10, 95% CI [1.01–1.19], p = 0.021) and with improved poor functional outcome after ischemic stroke at 90d (OR = 0.81, 95% CI [0.72–0.90], p = 1.79e-04) and motor recovery within 24 months after stroke (OR = 1.42, 95% CI [1.23–1.64], p = 2.15e-06). In MVMR, SBP and DBP significantly attenuated the causal effects of SUA on AS, IS, and functional outcome after ischemic stroke at 90d and motor recovery within 24 months after stroke. Further mediation analyses showed that SBP mediated 52.4 and 34.5% of the effects of SUA on AS and IS, while DBP mediated 28.5 and 23.4% of the causal effects, respectively. Conclusion This study supports the dual role of genetically predicted SUA in increasing stroke risk, especially ischemic stroke risk, and in improving functional outcome and motor recovery. SBP and DBP are key mediators lying on the causal pathways of SUA with AS and IS.